Organic-Inorganic Nanoscale Composites : Optical Properties as a Function of Anisotropic Orientation - Miller, Eric J.; Richards, Connor J.; Reitano, Nicholas M.; Lobermeier, Kyle L.; Dahl, Jennifer A. (My University, 2017)
Previous studies in our lab demonstrated the fabrication of covalently cross-linked soft networks of hydrophobic gold nanoparticles with the aid of a Langmuir trough. These composite materials exhibited greater mechanical integrity than comparable non-cross-linked networks, and these films can be cast upon planar or textured substrates with no disruption of the array. This methodology can be extended to arrays of anisotropic nanomaterials such as nanorods, whose optical properties are expected to be dependent upon final orientation (either side-by-side or end-to-end) of the finished cross-linked composition. Here, hydrophobic gold nanorods were synthesized and cast upon an air-water interface within a Langmuir trough. When this film is isometrically compressed to low surface pressures (~2 mN/m), end-to-end configurations of the film are favored, while side-by-side configurations, where the longitudinal axes of the nanorods are aligned with the surface normal of the air-water interface, are favored at higher surface pressures (>10 mN/m). Once the desired nanorod orientation is achieved through surface compression, the nanorods can be covalently cross-linked and transferred to a solid substrate for characterization of structure and optical properties. Likely applications of these materials include components of photovoltaic devices, optoelectronic circuits, and chemical-sensing membranes.
Color poster with text, charts, images, and graphs.
Keywords: Nanocomposites; Nanostructured materials; Posters